Complete genome sequence of Anaerococcus prevotii type strain (PC1T). Issue 2 (September 2009) - LaButti, Kurt; Pukall, Rüdiger; Steenblock, Katja; Glavina Del Rio, Tijana; Tice, Hope; Copeland, Alex; Cheng, Jan-Fang; Lucas, Susan; Chen, Feng; Nolan, Matt; Bruce, David; Goodwin, Lynne; et al.
Abstract Anaerococcus prevotii (Foubert and Douglas 1948) Ezakiet al. 2001 is the type species of the genus, and is of phylogenetic interest because of its arguable assignment to the provisionally arranged family 'Peptostreptococcaceae '.A. prevotii is an obligate anaerobic coccus, usually arranged in clumps or tetrads. The strain, whose genome is described here, was originally isolated from human plasma; other strains of the species were also isolated from clinical specimen. Here we describe the features of this organism, together with the complete genome sequence and annotation. This is the first completed genome sequence of a member of the genus. Next toFinegoldia magna, A. prevotii is only the second species from the family 'Peptostreptococcaceae ' for which a complete genome sequence is described. The 1, 998, 633 bp long genome (chromosome and one plasmid) with its 1852 protein-coding and 61 RNA genes is a part of theG enomic E ncyclopedia of B acteria and A rchaea project.